2010
DOI: 10.1098/rspb.2010.1591
|View full text |Cite
|
Sign up to set email alerts
|

Defining individual quality over lifetimes and selective contexts

Abstract: Individual quality has been measured as a variety of different traits and in several different contexts. However, the implications of such measurements in terms of overall fitness are less straightforward than has generally been appreciated. Here we outline some key issues in this regard that have yet to be addressed. Specifically, we consider the importance of both variation in selection on individual and multivariate suites of traits, and of context-specific plasticity in allocation strategies. We argue that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 85 publications
(110 reference statements)
2
56
0
Order By: Relevance
“…[21,23]), it may also result in decrease in fitness in other selective contexts (but see [66]). The fitness costs to expressing a poor bite force in terms of total selection (see [67,68] for discussion) might therefore outweigh the energetic costs of bite force development. Since our results show that bite force does not appear to be 'protected' from resource allocation in this way, a more likely possibility is that honesty may be maintained in nature via receiver-dependent costs if deceptive signallers are exposed through escalated combat with 'honest' individuals (cf.…”
Section: Discussionmentioning
confidence: 99%
“…[21,23]), it may also result in decrease in fitness in other selective contexts (but see [66]). The fitness costs to expressing a poor bite force in terms of total selection (see [67,68] for discussion) might therefore outweigh the energetic costs of bite force development. Since our results show that bite force does not appear to be 'protected' from resource allocation in this way, a more likely possibility is that honesty may be maintained in nature via receiver-dependent costs if deceptive signallers are exposed through escalated combat with 'honest' individuals (cf.…”
Section: Discussionmentioning
confidence: 99%
“…bite force and head size; Cameron et al, 2013). In fact, many studies have found that certain individuals outperform others in all tasks, a phenomenon that has invoked a recent surge in research on the concept of 'individual quality' (Van Damme et al, 2002;Wilson and Nussey, 2010;Lailvaux and Kasumovic, 2011;Wilson et al, 2014). However, few studies have been carried out examining similar performance traits in mammals and no study to our knowledge has examined the relationship between resource holding potential (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Total fitness is most clearly defined as the number of descendants produced by an individual relative to the average produced by other individuals in a population (Hunt et al 2004), and is affected by overall selection summed over several selective contexts (Hunt et al 2009;Lailvaux and Kasumovic 2011). As such, understanding the effects of a selective factor such as a pathogen on a given trait or traits in each of these broad contexts (e.g., natural selection versus sexual selection) is necessary if we are to understand how that factor ultimately affects total fitness.…”
Section: Introductionmentioning
confidence: 99%